Characterization of all-solid-state thin-film batteries with V2O5 thin-film cathodes using ex situ and in situ processes - Jeon, EJ; Shin, YW; Nam, SC; Cho, WI; Yoon, YS (ELECTROCHEMICAL SOC INC, 2001)
An all-solid-state thin-film battery with a full cell structure of Li/LiPON/V2O5 /Pt has been fabricated. The structural and electrochemical properties of a thin-film battery fabricated by an irt situ and an ex situ process were compared. in the in situ process, LiPON (lithium phosphorus oxynitride) electrolyte thin film was deposited on the V2O5 thin film by radio frequency reactive sputtering at room temperature without breaking vacuum. After deposition of the amorphous LIPON, a thermal evaporator in a dry room grew Li metal film as an anode. According to the results of the ac impedance analysis after 500 discharge cycle tests, R-i and E-ct of a thin-film battery fabricated by the ex situ process are over ten times higher than those of the thin-film battery fabricated by the in situ process. The thin-film battery fabricated by the ex situ process showed high capacity reduction because of the high R-i and R-ct. This result indicated that the cyclability of the thin-film battery strongly depends on the interfacial stability between the solid electrolyte and the cathode during intercalation and deintercalation of Li ions. Therefore, the iii situ process holds promise for the high performance of all-solid-state thin-film batteries. (C) 2001 The Electrochemical Society. All lights reserved.
Keywords: LITHIUM BATTERIES; MICROBATTERIES; ELECTROLYTE